Fuzzy Comprehensive Evaluation of Happiness Index of Nine Cities in Pearl River Delta Based on AHP - Aili Xie; Lianhua Liu; Longyi Qin (Journal of Mathematics)
With the development of China’s economy and the improvement of national income level, people’s living demands have shifted from food and clothing to happiness, so happiness has become an important indicator to measure the performance of government performance. Scientific measure of residents’ happiness is an important research topic for scholars, but the academic quantitative research on Chinese residents’ happiness is less. A few quantitative studies often focus on the happiness of a single study subject at some time, and this paper uses the fuzzy comprehensive evaluation method to measure the nine cities in 2011–2018, not only the comparative happiness between horizontal cities and cities, and the study data longitudinal span from 2011 to 2018. A comparative study of multiple objects across space-time was conducted. Empirical results show that the happiness level of urban residents in the Pearl River Delta has three characteristics: regional structure differentiation, urban group aggregation, and siphon effect in central cities, and the corresponding policy suggestions are put forward according to the results of the empirical research.